A Review on Ichat Messenger Application - Choudhary, Neha; Chauhan, Rakesh; Kumar, Nikhil; Singh, Shivendra kumar (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2023)
IChat Messenger is a freeware, cross-platform voice over IP (VoIP) chatting service. The programme enables the sending of text messages, voice calls, video calls, photos, and other media, as well as documents, user location, and other things. The programme can be accessed from desktop computers as well as mobile devices. Customers who use the service must supply a regular cell phone number. Initially, users could only communicate with one another one-on-one or in small groups of one-on-one users. WhatsApp announced a future business platform in September 2017 that will let businesses serve users' customer service needs. With the cross-platform mobile messaging service ichat, you may communicate with others without having to pay for SMS. On Android, ichat Messenger is accessible.All of the phones have messaging capabilities. It costs nothing to communicate your pals because ichat Messenger utilises the same internet data plan that you use for email and web browsing.